Mobilizing financial and technical assistance from non-traditional development partners (including non-profit international foundations) : a manual for CARICOM small and medium-sized enterprises (CDF BridgetownBB, 2011)
Covers mobilising financial and technical assistance by small enterprises from non-traditional development partners.
Keywords: SMALL ENTERPRISES